2021
DOI: 10.1029/2021gl093201
|View full text |Cite
|
Sign up to set email alerts
|

Subduction Polarity Reversal: Induced or Spontaneous?

Abstract: Both the negative buoyancy of the oceanic lithosphere and the plate convergence force are proposed to initiate new subduction (Gurnis et al., 2004;Stern, 2004;Stern and Gerya, 2018). The former dominates the process of spontaneous subduction initiation, while the latter drives the induced subduction initiation. Subduction polarity reversal (SPR), which always follows a prior intra-oceanic subduction (Brown et al., 2011;Dewey, 2005) is widely accepted to be the typical compression-induced subduction in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…In addition to the jamming effect of the buoyant plateau obstruction, the slab break‐off is thought to be another mechanism for SI (Almeida et al., 2022; Baes et al., 2011; Sun et al., 2021). The slab break‐off will induce mantle flow, causing the back‐arc lithosphere to rupture and be dragged down into the mantle wedge (Baes et al., 2011; Zhang & Leng, 2021). Our results find that if the old slab has been broken‐off, it can induce mantle flow to weaken the overlying plate (Figure S6 in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the jamming effect of the buoyant plateau obstruction, the slab break‐off is thought to be another mechanism for SI (Almeida et al., 2022; Baes et al., 2011; Sun et al., 2021). The slab break‐off will induce mantle flow, causing the back‐arc lithosphere to rupture and be dragged down into the mantle wedge (Baes et al., 2011; Zhang & Leng, 2021). Our results find that if the old slab has been broken‐off, it can induce mantle flow to weaken the overlying plate (Figure S6 in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results find that if the old slab has been broken‐off, it can induce mantle flow to weaken the overlying plate (Figure S6 in Supporting Information ). However, the weakening is not sufficient to cause lithospheric break‐up and onset of subduction in the youngest Solomon Sea Basin (about 40‐25 Ma) with a lower lithospheric density (Maunder et al., 2020; Zhang & Leng, 2021; Zhou & Wada, 2021). And, it is worth noting that the SI in our reference model is preceded to slab detachment caused by the newly subducting slab (Figure 2) rather than the old slab break‐off.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the petrologic evidence of strong extension has been used to distinguish spontaneous SI, such as the Izu‐Bonin‐Mariana (IBM) subduction zone (Arculus et al., 2015, 2019; Stern, 2004) and plume‐induced SI in the Caribbean (Baes et al., 2016; Gerya et al., 2015; Whattam & Stern, 2015). In contrast, polarity reversal is considered to be a typical induced SI in many categories (Crameri et al., 2020; Lu et al., 2021; Stern, 2004; Stern & Gerya, 2018; Zhang & Leng, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fragments of the previous subducting plate are naturally preserved during polarity reversal, which witnesses the whole process of subduction termination and (re)initiation and provides a favorable condition for revealing the dynamics of induced SI. Previous studies have shown that mantle avalanche (Pysklywec et al, 2003), arc-continent collision (Baes et al, 2011b;Chemenda et al, 2001;Clift et al, 2003;Johnson & Jaques, 1980;Konstantinovskaia, 2001;Ustaszewski et al, 2012;Zhang & Leng, 2021), and postsubduction accretion (Faccenda et al, 2008;Liu et al, 2021;Nair & Chacko, 2008;Simakin, 2014;Tao et al, 2020;Vogt & Gerya, 2014) can all induce subduction polarity reversal. Oceanic plateaus are widely distributed in the oceans (Figure S1).…”
mentioning
confidence: 99%